Design of Electronic Elementary Material Learning Module on Vocational Higher Education - Rahmadani, Ade Fitri; Hidayat, Hendra; Syahmaidi, Eril (International Journal of Scientific Research and Management (IJSRM), 2018)
This study aims to describe the design of a valid Learning Module for Elementary Elementary subjects. This research type is research of development by using 4D model that is definition stage (define), design stage (design), development stage (develop), and dissemination stage (disseminate). This study looks at whether the designed module is valid, then conducted expert test, namely expert design of Elementary Electronic Learning Module and expert readings Elementary Electronic Learning Module. Aspects that are tested to experts are aspects of the material in the learning module, aspects of presentation on learning modules and aspects of language and legibility. The results showed that the basic Electronic Elementary Learning Module by experts is valid. Then it can be concluded that the Module on Higher Education Vocation is valid